Workers’ insurgency and repression in Argentina in the 1970s: Class struggle in the transformation of capital accumulation. An analysis based on the struggle of the auto workers - Guevara, Sebastián (2025)
The article studies the process of political mobilisation and repression that auto workers in Argentina underwent between 1970 and the beginning of the 1980s, within the general context of the «international cycle of class struggle». It analyses them in the light of their relationship with the process of transformations that the global process of capital accumulation underwent, with its epicentre in the crisis of 1972-1982, which resulted in changes in the international division of labour. It is argued that the particular characteristics developed by the political process in Argentina can be explained by the specific way in which it participates in this international division of labour.